Developing a group intervention program to promote the spirituality (GIPS) for mothers of intellectually disabled children and assessing its effectiveness on marital satisfaction - akram hasani; hamid alizadeh; baghr ghobaribonab; Shahla Pezeshk; Farangis Kazemi (مجله علوم روانشناختی, 2020)
Background: The educational, educational, and rehabilitative difficulties of children with intellectual disabilities have caused their parents numerous difficulties and obstacles. Mothers of these children have more time to develop and empower their children because of their stronger emotional bond and a stronger role in their child's education and education. They are dedicated to meeting their needs, so they are more vulnerable to physical and mental problems. Aims: The purpose of this study was to develop a group education program to promote spirituality and its psychological consequences for mothers of children with intellectual disabilities. Method: The study was a pretest-posttest with control group. 36 mothers were selected by random sampling method and assigned to experimental and control groups. Research tools include Parsian & Dunning (2009) Spirituality Scale, Enrich Fowler & Olson Marital Satisfaction Scale (1989), and researcher-made spirituality group training (2019). Data analysis was performed using univariate analysis of variance. Results: The educational program had significant effect on overall spirituality (P<0/05). There was a significant difference between the experimental and control groups in the overall dimensions of marital satisfaction in the post-test and follow-up stages (P<0/05). Conclusions: Spiritual intervention can be used to increase the marital satisfaction of mothers with mentally retarded children.